Emission savings through the COP26 declaration of deforestation could come at the expense of non-forest land conversion - Mishra, Abhijeet; Humpenöder, Florian; Reyer, Christopher P. O.; Beier, Felicitas; Lotze-Campen, Hermann; Popp, Alexander (IOP Publishing, 2024)
The majority of signatories to The United Nations Climate Change Conference in 2021 (COP26) made a declaration to end deforestation by 2030. Here, we quantify future changes in land use and associated CO2 emissions to examine the impact of ending deforestation by 2030 on global land dynamics and emissions using an open-source land-use model. We show that if the COP26 declaration to end deforestation is fully implemented globally, about 167 Mha of deforestation could be avoided until 2050, compared to a baseline scenario which does not have extended forest protection. However, avoided deforestation and associated emissions come at the cost of strongly increased conversion of unprotected non-forested land to agricultural land, while land-use intensification in most regions is similar compared to a baseline scenario. Global initiatives are needed to facilitate a common dialogue on addressing the possible carbon emissions and non-forest leakage effects due to the expedited loss of non-forested land under a policy aimed at halting deforestation by 2030.